Impact of pregnancy on autograft dilatation and aortic valve function following the Ross procedure. (18th December 2017) - Carvajal, Horacio G.; Lindley, Kathryn J.; Shah, Trupti; Brar, Anoop K.; Barger, Philip M.; Billadello, Joseph J.; Eghtesady, Pirooz
Abstract: Objective: The effects of pregnancy on autograft dilatation and neoaortic valve function in patients with a Ross procedure have not been studied. We sought to evaluate the effect of pregnancy on autograft dilatation and valve function in these patients with the goal of determining whether pregnancy is safe after the Ross procedure. Design: A retrospective chart review of female patients who underwent a Ross procedure was conducted. Patients: Medical records for 51 patients were reviewed. Among the 33 patients who met inclusion criteria, 11 became pregnant after surgery and 22 did not. Outcome Measures: Echocardiographic reports were used to record aortic root diameter and aortic insufficiency before, during, and after pregnancy. Patient's charts were reviewed for reinterventions and complications. Primary endpoints included reinterventions, aortic root dilation of ≥5 cm, aortic insufficiency degree ≥ moderate, and death. Results: There were 18 pregnancies carried beyond 20 weeks in 11 patients. There was no significant difference in aortic root diameter between nulliparous patients and parous patients prior to their first pregnancy (3.53 ± 0.44 vs 3.57 ± 0.69 cm, P = .74). There was no significant change in aortic root diameter after first pregnancy (3.7 ± 0.4 cm, P = .056) although there was significant dilatation after the second (4.3 ± 0.7 cm, P = .009) and third (4.5 ± 0.7 cm, P = .009) pregnancies. Freedom from combined endpoints was significantly higher for patients in the pregnancy group than those in the nonpregnancy group ( P = .002). Conclusions: Pregnancy was not associated with significantly increased adverse events in patients following the Ross procedure. Special care should be taken after the first pregnancy, as multiparity may lead to increased neoaortic dilatation.